Efeitos do treinamento de força no músculo esquelético de ratos jovens e senis - Lopes, Giselle Nunes (2013)
Introduction: The skeletal muscle is the largest tissue present in vertebrates and is involved in locomotion, posture and breathing movements. It is composed of elongated, cylindrical and multinucleated muscle fibers with fat droplets in the sarcoplasma, known as intramyocellular lipid (IMCL) used as energy during exercise. Another source of energy used by the muscle is the carbohydrate stored in the body as glycogen, which is stored in the liver and muscle fibers. Muscle fibers are also surrounded by an extracellular matrix (ECM) formed, among other components, by collagen, mainly types I, III, IV and V. The aging process is associated with loss of muscle mass, muscle strength and function, increase of IMCL, reduction in glycogen synthesis with consequent insulin resistance, and also fibrosis and deposition of ECM. On the other hand, strength training (TF) is considered appropriate intervention to modify, minimize or reverse some physiological changes in skeletal muscle, as a result of aging. Thus, this study aimed to assess the cross section area of skeletal muscle fibers, amount of IMCL, glycogen content and MEC properties of the gastrocnemius (GAM) and soleus (SO) of young and senile rats after TF protocol. Methods: 28 rats were randomly divided into 4 groups: Youth (J); Old(S); Youth who underwent strength training (JT); Old who underwent strength training (ST). The animals performed strength training protocol consisting in climb a vertical ladder with weight strapped in their tails of 65%, 85%, 95% and 100% of the maximum load of the animal 3x a week for 12 weeks. CSA of muscle fibers, detection of collagen and identification of adipocytes in the GAM and SO muscles, beyond determinations of glycogen in the liver and skeletal muscle were performed. Results: Senile animals had lower CSA values, greater amount of IMCL, as well as of connective tissue in both muscles, but did not change the glycogen content in liver and muscle. After TF, the CSA increased in young and old animals in both muscles, the reduced IMCL in SO muscle of old animals, connective tissue decreased in young and old animals in both muscle and, finally, the glycogen content increased in liver and muscle of young and old animals. Conclusion: The strength training protocol in old rats was able to increase the CSA, decrease IMCL, increase of stored glycogen and decrease the connective tissue present in GAM and SO muscles. These results showed that there are changes in muscle fiber size, in the quantity of IMCL, in glycogen storage and in properties of the ECM of the GAM and SO muscle after intervention, indicating that strength training minimizes some deleterious effects inherent aging.